The spatial econometrics of elephant population change: A note - Björn Frank; Per Botolf Maurseth (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
While previous research found no other variable than corruption to have a negative impact on (the growth rate of) the African countries' elephant populations, we show that one further significant impact is exerted by what one might all neighbourhood effects. Elephants travel long distances, often crossing borders. Using spatial econometric tools, we find that elephant population changes in one country have a positive impact on elephants in neighbouring countries. Our results have possible policy implications, as they suggest that the spatial clustering of funds and of conservation efforts makes sense if the endangered species move across borders.
Keywords: R15; Q20; 330; Elephants; Spatial econometrics; Corruption and Ecology